The effect of float seedling growth media combination and particle size distribution on germination and biometric characteristics of tobacco seedlings (Nicotina tabacum) - Masaka, Johnson; Musundire, R.; Gondongwe, L. (Academic Journals, 2021)
An experiment was conducted for 20 weeks under float bed system in which nine tobacco seedling growing media mixed in different combinations based on particle size distribution of pine bark and coal rubble were studied. The objective of this study was to determine the effect of these different media combinations on the physical properties of the media blends; seed germination and biomass characteristics of tobacco seedlings in float tray system. The study was conducted at Kutsaga Research Station (17°52’ S; 31°02’ E, elev. >1500 m) near Harare in Zimbabwe. The experiment was designed as a Randomized Complete Block with three replicates. Study results show that media particle size distribution, combinations of pine bark and coal rubble media components had a comparatively significant effect on the total porosity of media blends while their influence on bulk density was largely insignificant. All media combinations in which the small to medium size pine bark particles (T5 and T8) contributed the bulk of media mass (90%) had the highest total porosities (70.2 and 70.1%) while the no-pine bark component treatment had the lowest (49.9%) total porosity (T6). The media combination that generated a total porosity of nearly 50% (T6) supported amplified initial germination counts. While a large body of research results elsewhere have indicated that the presence of sand or coal rubble components in media combinations tend to amplify spiral rooting counts of tobacco seedlings in float trays due to increased compaction associated with their high densities, our results have shown that it was the hydrology of the media combination that had a large influence on spiral rooting. The lowest initial tobacco germinations or increased seedling mortality places a reduced burden on the media nutrient resources thereby increasing the nutrient compensatory effect on growth of stems observed in T3 float trays.